THE EFFECT OF PREPOSITION AND VOCABULARY MASTERY ON STUDENTS’ WRITING DESCRIPTIVE TEXT - Teti Herawati; Gustaman Saragih (Universitas Indraprasta PGRI, 2021)
Abstract: This study aims to determine: 1) The effect of preposition and grammar mastery on students writing descriptive text. 2) The Effect of the preposition on students writing descriptive text. 3) The Effect of vocabulary mastery on students writing descriptive text. The Affordable population is class X of 1 Vocational School Rancaekek, Vocational School Majalayal. The sample of the research is 75 respondents in this study. The method of this current research used surveys. Inference analyses used are random and multiple linear regression. The results of the study show: 1) There is a significant effect of preposition and vocabulary mastery on student writing descriptive text; this is evidenced by the acquisition of Sig. = 0,000 <0,05 and F observe = 9,266; 2) there is a significant effect of the preposition on student writing descriptive text. This is evidenced by the acquisition of Sig. = 0,011<0,05 and T observe = -2,614.3. 3) There is a significant effect of vocabulary mastery on students writing descriptive text; this is evidenced by the acquisition of Sig. 0,003<0,05 and T observe = 3,058.Keywords: preposition, vocabulary mastery, descriptive text